PENDIDIKAN INFORMAL DAN PEMBENTUKAN KARAKTER(Suatu Tinjauan Kontribusi Ibu Dalam Pembentukan Karakter Anak) - Kaimuddin, Kaimuddin (An - Nisa`, 2010)
Abstract,: informal education and caracter building a study of motherâs contribution in caracter bullding. The main case that wil be explored in this reseach is who is the mother in familyâ s education environment? And what is the role of mother in building child caracter? This research indicates that mother has a big role in determining caracter building of child. Mother is the main and the first educator or teacher for her child. By felling a soft love from their mother, the child has muchÂ  time to have a good behaviuor because of getting a good initation. So, the contribution of mother determines caracter building ofchild.